TUJIA FOLKSONG IN CHONGQING, CHINA - wenzhe, liu; Karin, Khomkrit (Fine Arts Journal: Srinakharinwirot University, 2019)
This article is written from the Thesis entitled “An Analysis Tujia Folk Song in Chongqing, China” There are two objectives: 1) categorize types of music and 2) to analyze the element of the songs by using qualitative methods and the music research methodology. The data were collected in Fengmu Town, Tujia Autonomous County, Shizhu County, Chongqing City, China. From the samples who are artists and audiences. The results of the study show that there are 426 Tujia folk songs in Chongqing, and these songs can be categorized into 3 groups of lyrics which are 184 Love Song, 108 Labor Song, and 134 Natural Song. In term of the length, there are 238 short songs and 188 long songs. Additionally, the results of the study review that there are 5 Music styles and sounds including C, D, E, G and A and the 2th - 14th intervals with up and down serrated movement are applied to perform these songs.